2016
DOI: 10.1007/s10142-016-0483-2
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting cobalt chloride preconditioning to prevent hypobaric hypoxia-induced damage: identification of global proteomic alteration and key networks

Abstract: Several studies have supported the hypoxia mimetic roles and cytoprotective properties of cobalt chloride in vitro and in vivo. However, a clear understanding of biological process-based mechanism that integrates the available information remains unknown. This study was aimed to explore the potential mechanism of cobalt chloride deciphering its benefits and well-known physiological challenge caused by hypobaric hypoxia that reportedly affects nearly 24 % of the global population. In order to explore the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…This study, for the first time, reveals the universally perturbed pathways in both rat and human unhindered by differing conditions of hypoxic exposure. The collective studies (as shown in Supporting Information Data File S1) provide proteomic investigations of the plasma or specific tissues where subject was either human or rat . Some studies showcase only DE proteins but stop short of providing information regarding the processes that these proteins will affect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study, for the first time, reveals the universally perturbed pathways in both rat and human unhindered by differing conditions of hypoxic exposure. The collective studies (as shown in Supporting Information Data File S1) provide proteomic investigations of the plasma or specific tissues where subject was either human or rat . Some studies showcase only DE proteins but stop short of providing information regarding the processes that these proteins will affect.…”
Section: Discussionmentioning
confidence: 99%
“…The datasets taken were from the authors’ previous publications regarding effects of HH on proteome and a few other select publications regarding the same [, ] for a total of 154 DE proteins. The datasets were chosen on the basis of two criteria.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generation of Co-substituted myoglobin is used in designing artificial myoglobin-based oxygen carriers (Neya et al, 2014). In addition, cobalt preconditioning also affects other key networks, including lipid metabolism and cell cycle regulation (Ahmad et al, 2016).…”
Section: Mechanisms Of Physiological Functionmentioning
confidence: 99%